DAYA TERIMA DAN KANDUNGAN PROTEIN SERTA ZAT BESI PADA COOKIES DENGAN SUBSTITUSI TEPUNG JEWAWUT (Setaria italica) DAN TEPUNG IKAN KEMBUNG (Rastrelliger Kanagurta L.) - Hendrayati Hendrayati; Fatmawaty Suaib; Abdullah Tamrin; Nur Yani (Media Gizi Pangan, 2022)
ABSTRACT The availability of nutrients that a person needs can be met from other than main meals and snacks. One of the snacks orsnackswho is becomingtrendiscookies. Cookies generally contain high energy, fat and sodium but lack protein and iron as well as fiber. If cookies are used as a snack that can overcome nutritional problems, for example stunting toddlers, the snack besides containing enough energy also has high protein and iron content. Substitution is done to increase the nutritional value of a product. Sources of food that can be used as snacks that are rich in protein and iron include barley flour and mackerel flour. This manuscript is the result of research that aims to determine the acceptability and content of protein and iron incookieswith the substitution of barley flour and mackerel flour as an alternative healthy snack. This research is an experimental research. The manufacture of cookie products with the substitution of millet flour and mackerel flour was carried out at the Food Technology Laboratory and the acceptability test was carried out in the organoleptic laboratory of the Department of Nutrition, Poltekkes, Ministry of Health, Makassar. Cookies made as many as 4 (four) formulations. Analysis of protein content using the methodMicro Kjedhaland substanceairon using method spectrophotometer. Test resultsKruskal WallisOn acceptability, from the assessment of 25 untrained panelists, the formulation with a concentration of 15% millet flour and 5% mackerel flour was the favorite in the organoleptic test. Protein and iron content in 1 serving (40 g) contains 5.28 g protein and 2.86 mg iron. Further researchers can analyze other nutrients such as fat, folic acid, vitamin B6, vitamin B12, so that these cookies can be used as a snack in overcoming anemia, as well as consumer acceptance tests and shelf life tests. Keywords: Cookies, millet, puffer fish, protein, iron   Keywords: Cookies, Iron, Millet, Protein , Puffer fish